Social Participation of the Russian and Armenian Students in the Socio-Cultural Development of Cities - M. V. Pevnaya; E. A. Shuklina; A. N. Tarasova; L. A. Asoyan (Высшее образование в России)
The article was prepared on the basis of an international comparative study – a sociological survey of students from regional universities from 37 cities in the Sverdlovsk region of the Russian Federation and 20 settlements of the Shirak region in the Republic of Armenia (targeted sample, No. = 715). The authors explore the potential for social participation of students from countries with a common political background of post-socialism and cardinal differences in the cultural and historical heritage of urban spaces.The purpose of this article is to determine the potential for social participation of students of regional universities in Russia and Armenia and the subjective factors that determine their activity in the development of cities. The article analyzes the experience of volunteering, as well as the willingness of students to different types of constructive social participation in urban development. To identify factors that activate the social participation of students, a discriminant analysis has been used. Discriminant models were constructed dividing groups of students from different countries with a high and low degree of readiness for social participation, as well as into groups with and without volunteering experience. The authors argue that Russia and Armenia are characterized by an identical structure of student involvement in volunteer activities, but the level of students’ readiness for social participation in urban development in the countries under consideration is different. For Armenian students, not only the willingness for social participation is higher, but also the practices themselves are more associated with active socio-cultural activities in the urban space. Two factors that determine the experience of real participation in the socio-cultural development of cities are characteristic of both Russian and Armenian students. The real experience of volunteering is more likely to be acquired by those students who are motivated to receive information about the culture and history of their cities, as well as the ability to see and identify significant cultural and historical objects where they live and study. In the Russian scenario, the importance of the city, the need for its development increases for students if they, being armed with certain knowledge about its culture and history, consider that the city is an interesting object (including a tourist one) for promotion. For Armenian students, knowledge of the culture and history of their place of birth is a basic factor that shapes their interest in further exploring their cities, the desire to make them better.